Perceptions and practices of sexual and reproductive health in the health team of the Santa Teresita-Cerrillos Hospital and in women from the locality of Cerrillos, Salta, Argentina - Paula Ulivarri (Social Medicine Publication Group, 2019)
This article presents a synthesis of research results from the study: ¨Perceptions and practices of sexual and reproductive health in the health team of the Santa Teresita-Cerrillos Hospital and in women from the locality of Cerrillos, Salta, Argentina: Multiparity in young women and local health actions linked to Sexual and Reproductive Health". The method chosen was qualitative, based on Grounded Theory. In-depth interviews were conducted with women who had more than two children, and with the health team of Santa Teresita Hospital, Cerrillos, Salta. Through the employment of diverse data collection techniques, as well as through Grounded Theory analysis strategies, the principle of right to health and respect towards others emerges as a relevant result. At the same time, discrepancies were found between individuals´ healthcare needs and their perception of the institution´ accessibility. I expect the results to serve as a foothold for the generation of local health policies that answer the needs of women while respecting the socio-cultural context, from a law and gender perspective.